Concurrent radiotherapy and weekly gemcitabine treatment of locally advanced squamous cell carcinoma of head and neck - Singh, K. K.; Jayanthi, Chavva; Nikam, Bhushan; Kharde, Rohan (International Journal of Research in Medical Sciences, 2017)
Head and neck cancers are not curable yet but survival and local control has been increased due to concurrent treatment approach. Study was conducted to assess the role of concurrent Gemcitabine (2'2' Difluro Deoxycytidine) along with radiotherapy in treatment of Head and Neck cancers and to assess local control as well as disease free survival achieved due to chemoradiation. 100 patients were enrolled in this study, 50 patients received Radiotherapy (Group A- Control group) alone and 50 patients received Concurrent Chemoradiotherapy (Group B- Study group). Patients in study group received Gemcitabine 200mg/m2 on weekly basis for 5-7 cycles over 30 mins. Radiation delivered after 2 hours of IV infusion. Conventional radiotherapy was given in dose ranging from 66-70Gy in 33-37# for 6-7weeks.In this study, Grade 3 mucositis and Grade 2 pharyngeal toxicity were common i.e, 56% and 54% respectively in study group and 30% and 38% respectively in control group. Hematological toxicity i.e., Grade 1 leucopenia was seen in 28%. Even though the toxicities were high in study group compare to control group but they were tolerable and acceptable. The response was better in concurrent group than radiotherapy alone (Control group) CR 52% vs 40%, PR 34% vs 36% and SD 14% vs 24%. Concurrent use of gemcitabine and radiotherapy is a effective modality in treatment of head and neck cancers with acceptable toxicity. Improved local control shows that Gemcitabine acts as a sensitizers and has synergistic action along with radiotherapy.